S100/RAGE-Mediated Inflammation and Modified Cholesterol Lipoproteins as Mediators of Osteoblastic Differentiation of Vascular Smooth Muscle Cells - Chellan, Bijoy; Sutton, Nadia R.; Hofmann Bowman, Marion A. (Frontiers in Cardiovascular Medicine, 2018)
Arterial calcification is a feature of atherosclerosis and shares many risk factors including diabetes, dyslipidemia, chronic kidney disease, hypertension and age. Although there is overlap in risk factors, anti-atherosclerotic therapies, including statins, fail to reduce arterial and aortic valve calcifications. This suggests that low density lipoprotein (LDL) may not be the main driver for aortic valve disease and arterial calcification. This review focuses on modified LDLs and their role in mediating foam cell formation in smooth muscle cells, with special emphasis on enzyme modified non-oxidized LDL (ELDL). In vivo, ELDL represents one of the many forms of modified LDLs present in the atherosclerotic vessel. Phenotypic changes of macrophages and smooth muscle cells (SMCs) brought about by the uptake of modified LDLs overlap significantly in an atherosclerotic milieu, making it practically impossible to differentiate between the effects from oxidized LDL, ELDL and other LDL modification. By studying in vitro-generated modifications of LDL, we were able to demonstrate marked differences in the transcriptome of human coronary artery SMCs upon uptake of ELDL, OxLDL and native LDL, indicating that specific modifications of LDL in atherosclerotic plaques may determine the biology and functional consequences in vasculature. ELDL induces calcification of SMCs and this is associated with reduced mRNA levels for genes protective for calcification (ENPP1, MGP) and upregulation of osteoblastic genes. A second focus of this review is on the synergy between hyperlipidemia and accelerated calcification in vivo in a mouse models with transgenic expression of human S100A12. We summarize mechanisms of S100A12/RAGE mediated vascular inflammation promoting vascular and valve calcification in vivo.